KEBIJAKAN KEPEMIMPINAN PEREMPUAN DALAM PENDIDIKAN ISLAM: REFLEKSI ATAS KEPEMIMPINAN RKY RAHMAH EL YUNISIYAH - Syafwan Rozi; Devi Wahyuni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
Normative female leadership has very strong legitimacy, both theologically, philosophically, and legally. One of them is Presidential Instruction No. 9 of 2000 on gender mainstreaming in National Development which requires all National Development Program policies and programs to be designed with a gender perspective. Education that has a basic concept as a process of transfer of value and transfer of knowledge can not be separated from the role and participation of women with the condescendent characteristics, educators, compassionate which is the key to the world of education. However, when it comes to the issue of women's public role it is still a hot and central issue both locally and nationally. The issue is still very seriously debated by society scientifically. Is it proper and capable if women appear to lead the public in social sectors including education. If we do reflections from the past of women's leadership journey, the answer will be found. As the work of Rky Rahmah el Yunusiyyah very subtle in 1923 when establishing a special religious school for women Diniyyah Puteri. The girls' Special School is the main female pillar in Minangkabau to establish its influence in the ranks of religious leadership in the effort to combine religious education and modern education. How a Rahmah strugles with traditions/ customs and religions to assure her debut and her work in leading an institution. In the contemporary context that needs to be prepared by women is the empowerment of independent and intelligent attitudes, so that the potential possessed can develop optimally. Kepemimpinan perempuan secara normatif memiliki legitimasi yang sangat kuat, baik secara teologis, filosofis maupun hukum. Salah satunya adalah Instruksi Presiden (Inpres) nomor 9 tahun 2000 tentang pengarusutamaan gender dalam Pembangunan Nasional yang mengharuskan seluruh kebijakan dan Program Pembangunan Nasional dirancang dengan perspektif gender. Pendidikan yang mempunyai konsep dasar sebagai proses alih nilai (transfer of value) dan alih pengetahuan (transfer of knowledge) tidak bisa dilepaskan dari peran dan keikutsertaan kaum hawa dengan sifat pengayom, pendidik, pengasih yang merupakan kunci utama dunia pendidikan. Hanya saja, ketika menyinggung persoalan peran publik perempuan masih merupakan isu hangat dan sentral baik secara lokal maupun secara nasional. Persoalan tersebut masih sangat serius diperdebatkan oleh masyarakat. Apakah pantas dan mampu perempuan tampil memimpin publik di sektor sosial kemasyarakatan termasuk pendidikan. Kalau kita lakukan refleksi dari perjalanan kepemimpinan perempuan masa lalu akan ditemukan jawabannya. Seperti kiprah Rky Rahmah el Yunusiyyah sangat kentara pada tahun 1923 pada saat mendirikan Sekolah agama khusus untuk perempuan Diniyyah Puteri. Sekolah Khusus putri ini adalah pilar utama perempuan di Minangkabau untuk menegakkan pengaruhnya dalam jajaran kepemimpinan agama dalam upaya menggabungkan pendidikan agama dan pendidikan modern. Bagaimana seorang Rahmah bergulat dengan tradisi/adat dan agama untuk meyakinkan debut dan kiprahnya dalam memimpin sebuah lembaga. Dalam konteks kekinian yang perlu dipersiapkan kaum perempuan adalah pemberdayaan sikap mandiri dan cerdas, sehingga potensi yang dimiliki bisa berkembang seoptimal mungkin.